2006
DOI: 10.1086/511153
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Cold Gas at Intermediate Redshifts: Giant Metrewave Radio Telescope Survey Using Mg ii Systems

Abstract: Intervening H i 21 cm absorption systems at are very rare, and only four confirmed detections have been z ≥ 1.0 reported in the literature. Despite their scarcity, they provide interesting and unique insights into the physical conditions in the interstellar medium of high-z galaxies. Moreover, they can provide independent constraints on the variation of fundamental constants. We report three new detections based on our ongoing Giant Metrewave Radio Telescope (GMRT) survey for 21 cm absorbers at from candidate … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(46 citation statements)
references
References 23 publications
(23 reference statements)
2
43
1
Order By: Relevance
“… References: K06 –Kanekar et al (2006); G07 –Gupta et al (2007); K07 –Kanekar et al (2007); C07 – This paper. …”
Section: Observations and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… References: K06 –Kanekar et al (2006); G07 –Gupta et al (2007); K07 –Kanekar et al (2007); C07 – This paper. …”
Section: Observations and Resultsmentioning
confidence: 99%
“… b DLA candidates only and so neutral hydrogen column densities are unavailable, hence the upper limits in N H I for the non‐detections. Note that the sub‐DLA 0237−223 is common to both Gupta et al (2007) and Srianand et al (2007). …”
Section: Discussionmentioning
confidence: 99%
“…The H i 21‐cm absorption towards this absorber has a narrow profile that is well fitted with a simple two‐Gaussian model (Gupta et al 2007; Kanekar et al 2009b). As noted in , there is evidence of a core–jet structure in the 606 MHz VLBA image, which leads to a core covering factor of 0.32.…”
Section: Observationsmentioning
confidence: 87%
“…Gupta et al () have reported 21‐cm absorption from the z abs = 1.371 Mg ii system towards J0108−0037. Despite a low rest equivalent width of ∼0.3 Å for the Mg ii doublet, other absorption lines of weaker metal transitions are clearly seen even in the Sloan Digital Sky Survey (SDSS) spectrum.…”
Section: Gaussian Fits To 21‐cm Absorption Linesmentioning
confidence: 99%